High crimes ebook - Sebela, Christopher (High Crimes (2013)., 2019)
People die every year on Mount Everest. This year will be murder. Zan Jensen is on the run from her past. For now, she works as a climbing guide for rich tourists in Kathmandu. And on the side, she and her partner Haskell moonlight as high-altitude graverobbers, extorting money from the families of the many dead bodies that litter the peaks of the Himalayas. But when a body shows up at the summit of Mount Everest with a jackpot of state secrets embedded in its skin, they're put in the crosshairs of a government agency bent on recovering the bodyand eliminating any witnesses. Collecting the two-time Eisner-nominated comic by CHRISTOPHER SEBELA (CROWDED, SHANGHAI RED, We(l)come Back) and artist IBRAHIM MOUSTAFA (Jaeger, Mother Panic, James Bond), HIGH CRIMES is a high-altitude noir that's been called "the perfect thriller, with big stakes, damaged characters, dark pasts, and just the right ratio of humor-to-corpses" by CHELSEA CAIN, the New York Times bestselling author of the Archie Sheridan and Gretchen Lowell series. . Author: Christopher Sebela. Illustrator: Ibrahim Moustafa . 2019 Christopher Sebela & Ibrahim Moustafa.